ETHICS AND LAW IN HEALTH CARE - Rahmayanti; Yunita Ramadhani Panjaitan; Dewi Suryati; Novalina Br Kembaren; Wahyu Rahmatica; Edi Hidayat (PT. Radja Intercontinental Publishing, 2024)
Informed consent is a communication process between patients and health workers that aims to ensure that patients understand relevant medical information and provide consent for a medical procedure. This process is critical to protecting patient rights and meeting medical ethical standards. This journal presents a literature review on the concept of informed consent, the importance of its appropriate implementation, as well as challenges and strategies for implementing it in clinical practice. The discussion focuses on the key components of informed consent, such as providing adequate information, assessing patient capacity, and documenting consent. Apart from that, special issues related to informed consent are also discussed, such as in patients with cognitive impairment, children and emergencies. This journal concludes that effective implementation of informed consent requires commitment from health workers to ensure patient rights are protected and meet ethical standards for treatment.